2007
DOI: 10.1007/s00392-007-0517-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk predictors and frequency of cardiovascular symptoms occurring during cardiac rehabilitation programs in phase III-WHO

Abstract: Patients likely to experience cardiovascular symptoms in ambulatory rehabilitation can be identified by their medical history and perceived exertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 12 publications
1
16
0
7
Order By: Relevance
“…In contrast, 1 large scale epidemiological study of more than 674 000 patient exercise hours in a cardiac rehabilitation setting found that diabetes had no significant impact on cardiovascular symptoms or on events (Unverdorben et al 2007). This discrepancy in findings may be because the latter analysis was done on supervised exercise rehabilitation programs in patients who were medically cleared for exercise, while the former study was based on interviews of recent MI patients who were asked to report on the activities that they were doing in the hours before (or at the time of) the infarct.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In contrast, 1 large scale epidemiological study of more than 674 000 patient exercise hours in a cardiac rehabilitation setting found that diabetes had no significant impact on cardiovascular symptoms or on events (Unverdorben et al 2007). This discrepancy in findings may be because the latter analysis was done on supervised exercise rehabilitation programs in patients who were medically cleared for exercise, while the former study was based on interviews of recent MI patients who were asked to report on the activities that they were doing in the hours before (or at the time of) the infarct.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, we found that a majority of exercise training sessions occurred under supervision with a carefully targeted exercise intensity that would likely place the participants at overall low risk for an adverse event (i.e., mild to moderate intensity). When more vigorous exercise was performed, adverse events appeared more frequently and were of more clinical concern in some (Mittleman et al 1993;Bernbaum et al 1989;Schneider et al 1984Schneider et al , 1992Unverdorben et al 2007;Inoguchi et al 2000) but not all (Balducci et al 2004;Maiorana et al 2002;Mourier et al 1997;Giannopoulou et al 2005;Loimaala et al 2003;Matteucci et al 2006) studies. Thus, it remains unclear if the low incidence of reported ad-verse events documented in this analysis reflects the true safety of PA, screening-out of higher risk subjects prior to enrollment in trials, or less than optimal documentation of adverse events in many research studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations